Adolescent Medicine. - Greydanus, Donald E. (De Gruyter, 2012)
The bookś main focus is on the pharmacological treatment of the adolescent patient. It provides physicians and allied health professionals with pharmacological information covering all main specialities of internal medicine. The book emphasizes on the importance of youth-specific medical treatment of disorders and diseases.